2020
DOI: 10.1021/acssuschemeng.9b06283
|View full text |Cite
|
Sign up to set email alerts
|

Terpene-Based Natural Deep Eutectic Systems as Efficient Solvents To Recover Astaxanthin from Brown Crab Shell Residues

Abstract: The potential of natural deep eutectic systems (NADESs) to efficiently extract astaxanthin (AXT) contained in crab shell wastes was evaluated. Different terpene-based mixtures were prepared and characterized. Aiming at maximizing the AXT recovery, we evaluated the effect of operating temperature and time on the extraction performance. As a proof of concept, this paper also highlights the potential of NADESs for AXT extraction from shrimp shells, mussels, and Haematococcus pluvialis. The biological potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 70 publications
2
44
1
1
Order By: Relevance
“…The temperatures measured lie between 298 to 323 K at an increment of 5 K to study the chemical shifts that take place due to the H-bonded protons for the inter- and intramolecular bonds [ 31 , 32 ]. It has been shown that as the temperature of the sample is increased, a decrease in the intermolecular bonding takes place, which leads to an upfield shift of the H-bonded proton [ 33 ], as shown in Figure 2 . A temperature coefficient ( T coeff ) is obtained to study the magnitude of the shift and the type of H-bonding associated.…”
Section: Resultsmentioning
confidence: 99%
“…The temperatures measured lie between 298 to 323 K at an increment of 5 K to study the chemical shifts that take place due to the H-bonded protons for the inter- and intramolecular bonds [ 31 , 32 ]. It has been shown that as the temperature of the sample is increased, a decrease in the intermolecular bonding takes place, which leads to an upfield shift of the H-bonded proton [ 33 ], as shown in Figure 2 . A temperature coefficient ( T coeff ) is obtained to study the magnitude of the shift and the type of H-bonding associated.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is highly dependent on the compounds forming NADESs. In the study by Rodrigues et al [10], the NADESs used were mono-and diterpenic-based and showed that all the combinations had some toxicity in Caco-2 cells but could also inhibit the proliferation of HT-29 cells. Additionally, all terpenoid-based NADESs were able to inhibit the growth of S. aureus and E. coli.…”
Section: Toxicity Bioactivity and Biodegradabilitymentioning
confidence: 99%
“…An exhaustive revision of the literature shows that, apart from vegetables, plants, fruits or agricultural by-products, other natural matrices have also served as source of valuable compounds and as occur with previous sources, the use of NADESs as extraction solvents has been also carried out. In this sense, oils obtained from citric, cereals, olives, and palm [40][41][42][43][44][45][46] have been the products most widely evaluated using DESs, although flour [47], eggs [48] and milk [49] as well as nonagricultural by-products [10,50] have been also investigated. As can be seen in Table 3, the studies were focused on the search of different and varied types of molecules including phenolic compounds [40][41][42]46], flavonoids [40,43], terpenoids [10,42,44], proteins [48], lignans [45] or minerals [50].…”
Section: Using Des To Extract Bioactive Compounds From Other Natural Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al [95] prepared NADESs by (i) mixing various terpenes and also (ii) mixing various terpenes with saturated fatty acid (Table 2) as follows: (S)-(−)-perillyl alcohol 20 (POH), (±)-menthol (ME) and myristic acid (MA) were chosen as molecules that might donate a hydrogen bond through their hydroxyl group, while (S)-(−)-perillyl alcohol (POH), (±)-camphor (CAM), (±)-menthol (ME), eucalyptol (EU) and myristic acid (MA) might act as HBAs through their oxygen atoms. NADESs showed higher cytotoxicity than their corresponding physical mixtures, except for ME:MA eutectic system, prepared at an 8:1 ratio, compared with (±)-menthol and myristic acid physical mixture (PM).…”
Section: Therapeutic Deep Eutectic Solventsmentioning
confidence: 99%